Platforms as Proximity Enablers for Regional Development - Anastasia Panori (Platforms)
This study offers a theoretical contribution exploring the interplay between platforms, proximity, and regional development and highlighting platforms’ crucial role in transforming routines and enhancing regional capabilities. It argues that routines, defining regional organization and adaptability, exhibit high transformative potential through platforms. Additionally, the study outlines a five-phase platform integration process in the regional context—sensing, patterns, categories, relations, and sequences—emphasizing the progression from vague platform comprehension to nuanced perception. This symbiotic relationship between platform utilization and routine development reinforces regional adaptability, innovation, and success in a connected landscape, shaping new opportunities for proximity-driven development.